Field evidence of pore pressure diffusion in clayey soils prone to landsliding - Berti, Matteo; Simoni, Alessandro (Journal of Geophysical Research: Earth Surface, 2010)
The hydrologic behavior of shallow weathered soils commonly determines the propensity for slope failure. Here we use laboratory data and field data collected by an automated monitoring system to assess the character of pore water pressure responses in a natural clay slope subject to intermittent rainfall. Although we did not measure pore pressure distributions that triggered slope failure, we obtained three years of field data that provided reliable and largely reproducible documentation of transient pore pressure responses. At depths of tens of centimeters to a few meters below the ground surface, moisture and pressure sensors recorded relatively fast, transient responses to precipitation. The speeds of pore pressure pulses advancing downward in the saturated zone were much larger than those of advective fronts driven by gravity, and the amplitudes of the pulses attenuated with depth. Statistical assessment of 129 pressure head responses demonstrates that this behavior is consistent with predictions of a linear, one‐dimensional pore pressure diffusion model. However, the model best simulates measurements if diffusivity is treated as a calibration parameter and if initial moisture conditions match model assumptions. For regional assessment of slope stability, the predictive accuracy of the linear‐diffusion model is limited by inherent uncertainties in defining the initial conditions and in assigning the values of hydraulic parameters.